PENAMPILAN REPRODUKSI INDUK KAMBING KACANG DI KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Olivia Sendi Heluth; Feronica Parera; Jusak Labetubun (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2021)
The research was aimed to know how the reproductive performance of Kacang Does in Huamual District of West Seram Regency. The variable was observed includes first mating age, conception rate, post partum mating, kidding interval, litter size, pre weaning mortality, and doe reproduction index. The method used in this study was survey. The sample selected using purposive sampling method, while the identification of the respondents was used the simple random sampling. Based on research obtained, the reproductive performance of kacang does at this research location was based on first mating age 9.2 ± 3.08 month, conception rate 82.81%, post partum mating 4.10 ± 1.94 month, kidding interval 8.95 ± 2.23 month, litter size 1.88 head, pre weaning mortality 11.86% and doe reproduction index 2.24 head/doe/year.